Self-healing epoxy coating doped with Elaesis guineensis/silver nanoparticles: A robust corrosion inhibitor. (20th December 2021) - Ali Asaad, Mohammad; Bothi Raja, Pandian; Fahim Huseien, Ghasan; Fediuk, Roman; Ismail, Mohammad; Alyousef, Rayed
Highlights: Smart nanocontainers (MWCNTs-EG/AgNPs) acted as robust corrosion inhibitor. A simple and innovative technique to synthesise smart nanocontainers. The self-healing agent offered a barrier against corrosive species. Excellent repair of self-healing coating. Abstract: This paper reports the self-healing properties of novel epoxy coating comprised of multi-walled carbon nanotubes (MWCNTs) as nanocontainers loaded with 5% green inhibitor- Elaeis guineensis /silver nanoparticles (EG/AgNPs) that acted as robust corrosion inhibitor for mild steel against adverse seawater environment. The self-healing assisted anti-corrosion effectiveness of the inventive coating for mild steel under seawater exposure for 42 days was evaluated via polarisation resistance, electrochemical impedance spectroscopy, adhesion strength and visual inspections. Further, the coated mild steel surface was characterised using X-ray diffraction, atomic force microscope and scanning electron microscopy analysis. The microstructures of smart powder (MWCNTs-EG/AgNPs) were also screened by a variety of microstructures techniques. Results revealed an excellent self-healing functionality of the produced smart epoxy coating with satisfactory anticorrosion behaviour against seawater exposure. A maximum of 97.87% inhibition efficiency and a minimum of 0.0009 mm/year corrosion rate were recorded after 42 days of exposure. Furthermore, this smart coating disclosed superior corrosion inhibition abilities even after 42 days of submersion in seawater by weakened the lepidocrocite (γ-FeOOH), as a result of the release of Elaeis guineensis /AgNPs, which in turn acted as efficient corrosion inhibitors to repair or self-heal the damaged coatings on mild steel surface.